'To show or No-show'? Therapist Racial-ethnic Disparities in Clients' Nonattendance in Therapy. Issue 1 (2nd January 2019) - Kivlighan, D. Martin; Jung, Ae-Kyung; Berkowitz, Alayna B.; Hammer, Joseph H.; Collins, Noah M.
ABSTRACT: Clients' nonattendance in therapy poses a significant threat to the effective delivery of mental health services at university counseling centers. As such, researchers have investigated processes related to clients' nonattendance in an effort to increase treatment utilization and treatment outcomes. However, there is a paucity of research testing the impact of the therapist on clients' nonattendance patterns. Additionally, it is unknown whether therapists vary in the nonattendance of their racial/ethnic minority (REM) and White clients. Therefore, the present study sought to identify therapist effects in client nonattendance rates, and examine between-therapist disparities in REM and White clients' nonattendance patterns. Data for this study consisted of 275 REM and 341 White clients seen by 21 therapists at a large university counseling center. Results indicated that therapists accounted for 14% of the variability in clients' nonattendance. Additionally, therapist effects in nonattendance due to clients' REM status were identified, suggesting that therapists are a significant source of racial/ethnic disparities in clients' nonattendance. REM clients' nonattendance rates were higher compared to White clients for some therapists, but not others. Clinical implications and future research are discussed.